Konsep Tujuan Pembelajaran Bahasa Arab Berbasis Neurosains dalam Kurikulum Merdeka Belajar - Jamil, Sobrun; Nandang, Ade (STAINI Press, 2025)
The independent learning curriculum has various components that are able to support the working systems of the left and right brain simultaneously. The use of these working systems has the same correlation with the development of neuroscience concepts which is a development of knowledge that originates from human neurons. This research aims to determine the concept of Arabic language curriculum development in terms of the aspect of learning objectives combined with efforts to integrate interdisciplinary science based on neuroscience concepts. The research method used is qualitative research, descriptive analysis using library study data collection techniques. The results of this research show that neuroscience-based concepts have relevance to the concept of Arabic language learning objectives in the independent curriculum. This correlation is rooted in the concept of a neuroscience approach which combines cognitive, affective and psychomotor domains in the concept of learning objectives which combines a system of combining knowledge domains based on systems. the workings of the human left brain and right brain nerves. The implications of this research are that it provides a contribution regarding a concept of Arabic language learning objectives based on a neuroscience approach in its efforts to develop an independent Arabic language learning curriculum